EVALUATION OF CYTOKINES IL-12 AND IL-15 IN PATIENTS WITH AUTOIMMUNE CELIAC DISEASE IN NAJAF PROVINCE: IMPLICATIONS FOR IMMUNE RESPONSE - Dr. Eman Hamza Mohammed (European Science Publishing, 2024)
Celiac disease (CD) is a common immune-mediated intestinal disease. In genetically susceptible people, it is caused by gluten proteins found in barley, wheat, and rye. Screening for CD requires anti-gliadin antibodies (AGA), although high AGA levels are found in many immune-mediated skin diseases without gastrointestinal symptoms.
Keywords: Cytokines, IL-12, IL-15, Autoimmune, Celiac Disease, Immune Response, Najaf Province.